Effect of lung cancer surgery on quality of life. Issue 3 (1st March 2005) - Win, T; Sharples, L; Wells, F C; Ritchie, A J; Munday, H; Laroche, C M
Abstract : Background: Health related quality of life (HRQOL) after surgery is important, although very limited data are available on the QOL after lung cancer surgery. Methods: The effect of surgery on HRQOL was assessed in a prospective study of 110 patients undergoing potentially curative lung cancer surgery at Papworth Hospital, 30% of whom had borderline lung function as judged by forced expiratory volume in 1 second. All patients completed the EORTC QLQ-C30 and LC13 lung cancer module before surgery and again at 1, 3 and 6 months postoperatively. Results: On average, patients had high levels of functioning and low levels of symptoms. Global QOL had deteriorated significantly 1 month after surgery (p = 0.001) but had returned to preoperative levels by 3 months (p = 0.93). Symptoms had worsened significantly at 1 month after surgery but had returned to baseline levels by 6 months. Low values on the preoperative HRQOL scales were not significantly associated with poor surgical outcome. However, patients with low preoperative HRQOL functioning scales and high preoperative symptom scores were more likely to have poor postoperative (6 months) QOL. The only lung function measurement to show a marginally statistically significant association with quality of life at 6 months after surgery was percentage predicted carbon monoxide transfer factor (Tlco ). Conclusion: Although surgery had short term negative effects on quality of life, by 6 months HRQOL had returned to preoperative values. Patients with low HRQOL functioning scales, high preoperative symptom scores, and preoperative percentage predicted Tlco may be associated with worse postoperative HRQOL.